Considering extended right lobe grafts as major extended donor criteria in liver transplantation is justified - Lozanovski, Vladimir J.; Probst, Pascal; Ramouz, Ali; Arefidoust, Alireza; Ghamarnejad, Omid; Aminizadeh, Ehsan; Khajeh, Elias; Mehrabi, Arianeb (Transplant international, 2021)
The outcomes of split-liver transplantation are controversial. This study compared outcomes and morbidity after extended right lobe liver transplantation (ERLT) and whole liver transplantation (WLT) in adults. MEDLINE and Web of Science databases were searched systematically and unrestrictedly for studies on ERLT and its impact on graft and patient survival, and postoperative complications. Graft loss and patient mortality odds ratios (OR) and 95% confidence intervals (CI) were assessed by meta-analyses using Mantel-Haenszel tests with a random-effects model. Vascular and biliary complications, primary nonfunction, 3-month, 1-, and 3-year graft and patient survival, and retransplantation after ERLT and WLT were analyzed. The literature search yielded 10 594 articles. After exclusion, 22 studies (n = 75 799 adult transplant patients) were included in the analysis. ERLT was associated with lower 3-month (OR = 1.43, 95% CI = 1.09-1.89, P = 0.01), 1-year (OR = 1.46, 95% CI = 1.08-1.97, P = 0.01), and 3-year (OR = 1.37, 95% CI = 1.01-1.84, P = 0.04) graft survival. WL grafts were less associated with retransplantation (OR = 0.57; 95% CI = 0.41-0.80; P < 0.01), vascular complications (OR = 0.53, 95% CI = 0.38-0.74, P < 0.01) and biliary complications (OR = 0.67; 95% CI = 0.47-0.95; P = 0.03). Considering ERLT as major Extended Donor Criteria is justified because ERL grafts are associated with vasculobiliary complications and the need for retransplantation, and have a negative influence on graft survival.